Efektivitas Penerapan Perda Nomor 7 Tahun 2013 terhadap Penataan tan Pemberdayaan Pedagang Kaki Lima ti Gresik - Etis Fitriawati Nurjannah; Dodi Jaya Wardana; Hardian Iskandar (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
Street vendors (PKL) constitute an essential component of the informal economic sector in Gresik Regency, yet their presence often generates issues related to urban order, cleanliness, and aesthetics. This study aims to: (1) analyze the effectiveness of implementing Gresik Regency Regional Regulation Number 7 of 2013 concerning the Arrangement and Empowerment of Street Vendors, and (2) identify the obstacles faced by the local government in carrying out the regulation. This research employs a socio-legal method with a normative-empirical approach, utilizing statutory analysis, field observation, interviews, and documentation. The findings indicate that the arrangement and empowerment of street vendors have been carried out through the designation of trading locations, regulation of operating hours and physical facilities, establishment of requirements for becoming street vendors, and the enforcement of rights, obligations, prohibitions, and sanctions. The Gresik Regency Government has also undertaken relocation initiatives to designated areas. However, the effectiveness of the regulation remains hindered by limited human resources, weak monitoring systems, and low compliance among some street vendors. Overall, the implementation of Regional Regulation Number 7 of 2013 has been conducted but has not yet achieved optimal outcomes in ensuring order and promoting the independence of street vendors. Strengthened coordination, enhanced guidance, and improved regulatory systems are needed to support the sustainability of the informal sector in Gresik Regency.